The self in the mirror of the Scriptures: the hermeneutics and ethics of Paul Ricoeur - Ford, Amanda Kirstine (2012)
In 'Oneself as another' Paul Ricoeur considers the nature of selfhood concluding that it can only be understood as polyvalent. He uses narrative identity to show that because selves both “act and suffer” human identity is intimately tied with encounter with the Other. The ethical dimension is explored in a mediation between Aristotelian teleological ethics and Kantian deontological morality, resulting in phronēsis or practical wisdom. The book ends with a number of aporias, including the problem of identifying the internal voice, heard in the conscience – the voice of attestation. In a related paper, which provided the impetus for this thesis - “The self in the mirror of the Scriptures” - Ricoeur considers the issues of identity from a religious perspective.